Voice from Within: Student Teachers’ Perception on Factor Influencing Willingness to Speak English in Language Classroom at English Education Study Program of UIN Raden Fatah Palembang - ZAKIAH KURNIA (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
The need for good communication skill in English has become a demand that continues to increase. One frustration is that they have spent years studying English, but they still cannot speak it. Therefore in this case, it is necessary to know what are the things that influence willingness of the students to speak English in the language class. This study investigated the student teachers’ perception on factor influencing willingness to speak English in language classroom at English Education Study Program of UIN Raden Fatah Palembang. I used qualitative study with case study design. The participants of this study were nine students of English Education Study Program of UIN Raden Fatah Palembang in the academic year of 2016/2017. The participants were chosen by using purposeful sampling technique. I employed interview technique to collect the data. The result showed that a number of factors contributed to student teachers’ willingness to speak. These factors included motivation, selfbeliefs’, collocutor, and object discussion.